2009
DOI: 10.1007/s10067-009-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive plain X-ray findings in distinguishing early stage acute lymphoblastic leukemia from juvenile idiopathic arthritis

Abstract: Acute lymphoblastic leukemia (ALL) presenting with musculoskeletal pain may be difficult to distinguish from juvenile idiopathic arthritis (JIA). The objective of this study, which separates it from most studies investigating these two diseases, is to determine the role of plain radiography in the initial approach toward patients presenting with musculoskeletal symptoms and to look for signs suggestive of each of the two disease entities. X-rays of patients referred to our center for musculoskeletal symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Patient 3 also presented bilateral abnormal striation of the lower metaphyses. These radiographic features were not described in patients with sJIA 15 16…”
Section: Resultsmentioning
confidence: 92%
“…Patient 3 also presented bilateral abnormal striation of the lower metaphyses. These radiographic features were not described in patients with sJIA 15 16…”
Section: Resultsmentioning
confidence: 92%
“…Prior studies of arthralgia or arthritis in children with ALL are few. Joint pain was present at diagnosis in 16% in one study,13 whereas arthritis has been found to be present in 2–10% 4 15 20 21. Gur et al 22 studied the rheumatic manifestations preceding adult acute leukaemia and found that 3.6% presented as a reactive arthritis with asymmetric involvement of the large joints.…”
Section: Discussionmentioning
confidence: 88%
“…The clinical presentation, and the consequences of isolated joint involvement, however, is sparsely described 14–16. The main focus in the literature has been the differentiation of children with musculoskeletal symptoms caused by ALL from children with JIA 4 8 9 11 12 17–19…”
Section: Discussionmentioning
confidence: 99%
“…At the diagnosis of acute monoarthritis, CR of the involved joint should be performed, with two perpendicular views . The French Society for Radiology [90] strongly recommends CR of any site of focal bone pain in paediatric patients, with the goal of excluding a tumour, osteomyelitis, or a haematological malignancy [34, 97]. …”
Section: Resultsmentioning
confidence: 99%